Advantages and disadvantages of forensic audit - Postnikova, Vera (My University, 2014)
In Ukraine forensic audit is not well-developed, so our experts should adopt the experience of foreign counterparts.
Keywords: forensic audit; legal concern; судова перевірка; юридична проблема